Plan de Marketing Digital para la Empresa Café Indera de la Ciudad De Loja”. Periodo octubre 2019 – marzo 2020 - González Cevallos, Aníbal Leonardo (2020)
The present research work has as a general objective to DEVELOP A DIGITAL MARKETING PLAN FOR THE CAFÉ INDERA COMPANY in order to contribute to the development and strengthening of the company For the preparation of this work, it was based on three specific objectives; The first specific objective is to carry out a situational analysis of the company through internal and external analysis, with respect to the external analysis, an evaluation was made of the factors that have a greater positive and negative impact on the company; Through the PESTEC analysis, it is possible to investigate the level of incidence of political, economic, social, technological, ecological and competitive factors, through the use of the EFE matrix of external factors where the weighted result was 3.14, which indicates that the company is above the measure of effort, in which it must follow strategies that gather external opportunities in order to avoid possible threats that negatively affect the company and in turn identify the most important opportunities such as : economic stability, employment contracts, population increase in the province of Loja by 7.8% in the coming years, technological innovation and the use of the internet With the aforementioned opportunities, it is possible to determine the feasibility of generating marketing strategies through the use of digital tools, taking advantage of the use of technology to improve communication processes In objective number two it includes the market research, where the application of the interview to the manager of the company was carried out, the application of surveys to the 9 workers of the company and 378 surveys applied to the real clients of the company The internal analysis of the company took into consideration the different functional areas, and the respective determinants of success, which allowed developing advertising strategies to promote the products and services offered by the company. In this case, to determine the strengths and weaknesses, the EFI internal factor evaluation matrix was applied, where it was obtained as a result 2.88, in which it was possible to identify what its main strengths are: the company fully complies with its financial obligations, All workers have their adequate tools to carry out their work, however, among their weaknesses, they identified that the company lacks an organizational structure, does not have training programs for workers, there is not enough publicity about the products and services of the company in digital media and in turn the company does not have a marketing plan Based on the analyzes carried out based on the objective that mentions the realization of a situational diagnosis, the SWOT matrix, the MPC matrix or the competitive profile were identified, where the main coffee shops that represent the competition for the Coffee company were identified Indera are; “El Tamal Lojano” and “La Artesanal” The Café Indera company, in the BCG matrix allows to identify and know the products that have the highest incidence and participation in the market, in which it can be determined that the products of the Café Indera company have two star products that are Filtered Coffee and Tigrillo, which has great acceptance in the market, three products considered as money-generating cows that are: El Bolón de Verde, Tamales and Empandas de Verde, two questioning products were identified: The Fruit and Quimbolitos Salad, finally They identified 3 products that correspond to the dog quadrant that are: Dirty Mote, Sango, Empanadas de Yuca those products that will be considered by the manager to continue offering or replace them with new products. The Ansoff matrix identified that Café Indera, is in a current market with existing products For the objectives for the implementation of the Digital Marketing Plan where the first objective is proposed: The elaboration of a structural and functional organization chart for the Café Indera company where the different positions and hierarchy that it has that will have a cost are clearly detailed of $ 16.80, objective number two is proposed to make known to the company Café Indera through different digital tools the cost to execute this objective will be $ 5000, objective number three is on the implementation of digital tablets in all tables of The company Café Indera in order to improve your experience when making your consumption for the cost to meet this goal will be $ 1000 Finally, the respective conclusions and recommendations are presented with the results obtained in the development of this digital marketing plan in order to generate a competitive advantage and increase its market share.